5-year outcomes of iStent micro-bypass vs. Kahook dual blade goniotomy in open angle glaucoma - Ejaz Ansari (Graefe's Archive for Clinical and Experimental Ophthalmology, 2026)
Abstract Purpose Long-term comparison of efficacy and safety of i-Stent versus KDB goniotomy combined with phacoemulsification through to 5 years. Methods A retrospective chart review of 88 patients that received iStent or KDB in combination with phacoemulsification at a single centre between January 2014 and January 2019. Outcome measures were proportion of eyes achieving ≥ 20% reduction of IOP, drop dependence through to 5 years and change in visual field mean deviation (MD) at year 5 compared to baseline. Early to moderate stage of glaucoma. Results No significant difference between groups for IOP reduction ( p = 0.3) or visual field MD ( p = 0.85) at all time points through to 5 years. Significantly lower drop dependence favouring KDB at all time points ( p < 0.001 year 1; p = 0.02 year 5). Lower rate of secondary procedures following KDB (7.7% vs. 14% p = 0.48). Adverse events following iStent and KDB: hyphaema (5.5% v 10% p = 0.70), corneal oedema (8% v 2% p = 0.30), rebound anterior uveitis (5.5% v 2% p = 0.57). Complications resolved within 2 weeks with no serious incidents (loss of VA by ≥ 2 Snellen lines/ 0.3 logMAR). Conclusion Each procedure provided comparable long-term IOP reduction and visual field stability over five years. KDB goniotomy resulted in significantly less drop dependence throughout with fewer associated secondary procedures. Adverse events were infrequent and mild, with no serious complications observed.